Pengaruh Rangkaian Abjad Warna Terhadap Peningkatan Daya Baca Siswa-Siswi Kelas 1 MI Miftahul Ulum (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The influence of a color alphabet learning media to provide an understanding of memorizing an alphabet to improve the reading power of class 1 MI Miftahul Ulum students, where in this learning students are provided with a color alphabet teaching aid to make it easier for students to memorize the alphabet and improve their reading ability. In this study, the researcher formulated a problem whether color alphabet learning media would affect the reading ability of grade 1 students at MI Miftahul Ulum. In this research, the "qualitative" type is used, the researcher is the key, the data collection method is triangulation, and the data assessment is subjective, feeling tense, meaning that a "hypothesis" occurs. Based on the existing results, the level of reading memory ability of grade 1 students at MI Miftahul Ulum The use of color alphabet series media is relatively low, namely 40%. Furthermore, after applying the color alphabet series media, the reading memory ability of MI Miftahul Ulum class 1 students increased, reaching 80%, then looking at the existing results, the level of reading memory ability of MI Miftahul Ulum class 1 students after applying the alphabet series media color is high.